A multi-product maximin hazmat routing-location problem with multiple origin-destination pairs. (10th December 2019) - Beneventti G., Diego; Bronfman, Andrés; Paredes-Belmar, Germán; Marianov, Vladimir
Abstract: The United Nations define Supply Chain Sustainability as "the management of environmental, social and economic impacts, and the encouragement of good governance practices throughout the lifecycles of goods and services." (UN, 2015 ). We deal with the logistic network, an important component of the Supply Chain, in industries either generating or using hazardous material (HM) in some stage of their productive processes. A major concern when transporting HM or locating hazardous facilities is to minimize risks and hazards to the population and environment. Most studies on this issue only consider one type of HM and fail to differentiate populations with different degrees of vulnerability. This work addresses both the problem of locating hazardous facilities and routing HMs across a large, densely populated urban area, minimizing the associated costs and hazards imposed on the population. Populations, aggregated in centers, were differentiated into vulnerable populations, which are the hardest to evacuate in a short period of time, and non-vulnerable populations. Several types of HMs with different degrees of hazard were considered. We propose a multi-objective programming model with multiple origin-destination (OD) pairs that considers maximizing the minimum weighted distance between hazardous facilities and the exposed vulnerable population, maximizing the minimum weighted distance from HM transportation arcs to the exposed vulnerable population, minimizing the total hazard imposed on the non-vulnerable population, and routing and location costs. The methodology has been tested in the transportation network in the city of Santiago, Chile. Highlights: Efficient locations and routes are found for locating and transporting HAZMAT (HM). Multiple OD pairs are considered in the multiproduct HM routing-location problem. The population units (PUs) are segmented into vulnerable and non-vulnerable. Costs and hazards imposed to PUs are minimized. Hazards and severity of danger imposed by each HM on each PU have been considered.